A call for deeper insights into intramural pregnancy: An international data registry - Simrit Nijjar; Cecilia Bottomley; Davor Jurkovic (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Intramural pregnancy (IMP) is a rare and potentially life‐threatening uterine ectopic pregnancy implanted within the myometrium. Despite its recognition as a distinct clinical entity, diagnostic challenges and a lack of standardized management protocols persist. IMP occurs when a gestational sac implants into the myometrium beyond the endometrial‐myometrial junction, often following uterine trauma. Diagnosis is hindered by non‐specific symptoms and frequent misclassification. While ultrasound is the primary diagnostic tool, magnetic resonance imaging (MRI) may be needed in unclear cases. Treatment options range from expectant management to surgical intervention, but no consensus exists on the optimal approach. To enhance understanding and improve clinical outcomes, we propose an international IMP registry to collect data on diagnosis, treatment, and fertility outcomes. This collaborative effort aims to inform evidence‐based guidelines, facilitating accurate early diagnosis and optimized patient care.